Differences in physical fitness and subjectively rated physical health in Vietnamese and German older adults - Nguyen, Hung M.; Cihlar, Volker (Journal of cross-cultural gerontology, 2013)
This cross-sectional study aims to investigate the differences in physical fitness and subjectively rated physical health of Vietnamese and German older adults in a community dwelling. The Vietnamese sample was a random sample of 96 community-dwelling individuals aged 60 to 80 years; 50 % were women. Education is 0 % less than 5 years, 23.95 % 5 to 9 years, 47.91 % 10 to 12 years, and 28.12 % more than 12 years. The German sample was a random sample of 159 community-dwelling persons aged 59 to 90 years; 79.8 % were women. Education is 1.25 % less than 5 years, 40.25 % 5 to 9 years, 38.84 % 10 to 12 years, and 21.38 % more than 12 years. Senior Fitness Test and Short Form-36 were used as outcome measures. The Vietnamese sample shows significantly higher performance levels in motor abilities, i.e., aerobic fitness, strength, and flexibility. The Vietnamese sample indicates a lower difference in performance levels between age groups than the German sample. No differences in subjectively rated physical health factors were found. The higher performance levels of the Vietnamese sample might reflect a more active lifestyle throughout the life span, especially in socially mediated domains like living arrangements or labor work. Lower performance levels in the studied age groups of the German sample might lead to higher risks of cardiovascular diseases and proneness of falls. A more active lifestyle after retirement could contribute to a healthier, more capable, and more independent individual and collective aging. Subjectively rated health stated is a culturally mitigated domain and therefore might be independent of actual physical fitness levels.